2019
DOI: 10.1016/j.ultramic.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated electron energy loss and gain in an electron microscope without a pulsed electron gun

Abstract: We report on a novel way of performing stimulated electron energy-loss and energy-gain spectroscopy (sEELS/sEEGS) experiments that does not require a pulsed gun. In this scheme, a regular scanning transmission electron microscope (STEM) equipped with a conventional continuous electron gun is fitted with a modified EELS detector and a light injector in the object chamber. The modification of the EELS detector allows one to expose the EELS camera during tunable time intervals that can be synchronized with nanose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 26 publications
(16 reference statements)
4
44
0
Order By: Relevance
“…Table 2 summarizes the M x max numbers estimated from the peak fits of the spectra taken at the spontaneous EELS intensity maximum positions for each mode. Note that while higher light-driven plasmon populations are realized in high-irradiance pulsed experiments 57 , the values realized here are consistent with previous low irradiance cw experiments 59 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Table 2 summarizes the M x max numbers estimated from the peak fits of the spectra taken at the spontaneous EELS intensity maximum positions for each mode. Note that while higher light-driven plasmon populations are realized in high-irradiance pulsed experiments 57 , the values realized here are consistent with previous low irradiance cw experiments 59 .…”
Section: Discussionsupporting
confidence: 92%
“…As noted previously 51 and confirmed in our previous work 59 , the sEELS and sEEGS peaks have nearly the same amplitude and thus while the sEEL peaks are convolved with the LSPR peaks, we can unambiguously fit the sEEG peaks and thus de-convolve the sEEL and LSPR peaks (see supplemental information for peak fitting). Furthermore, Das et al 57 showed that the light-driven population of the plasmon mode (M x max ) can be estimated…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous-wave laser illumination of complex materials is feasible at intensities of 10 4 to 10 6 W/cm 2 (31, 32) and with field strengths of ~10 6 V/m, enough to produce substantial holographic image distortions (9) or spectral changes in photon-induced near-field electron microscopy (6,31). Nanosecond excitation can be used for alleviating thermal load (33). In contrast to femtosecond pump-probe microscopy and diffraction, which aim at tracking the evolution of a material after absorption of a femtosecond laser pulse, the main application of our electron microscopy will be investigations of electromagnetic phenomena that are triggered by the cycles of light (4) and not by the intensity envelope of pulses (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…To allow excitation of the sample by a laser beam or collection of its cathodoluminescence, a light injection/cathodoluminescence system has been installed in the objective lens. It is composed of a parabolic mirror placed above the sample which can be adjusted from outside the TEM column by micrometer screws [36]. We describe in the following the electron emission process and compute the temporal and spectral properties of the electron pulses.…”
mentioning
confidence: 99%